High Co-circulation of Influenza and Severe Acute Respiratory Syndrome Coronavirus 2. (28th November 2022) - Kubale, John T; Frutos, Aaron M; Balmaseda, Angel; Cerpas, Cristhiam; Saborio, Saira; Ojeda, Sergio; Barilla, Carlos; Sanchez, Nery; Vasquez, Gerald; Moreira, Hanny; Shotwell, Abigail; Meyers, Alyssa; et al.
Abstract: In the first 2 years of the coronavirus disease 2019 pandemic, influenza transmission decreased substantially worldwide, meaning that health systems were not faced with simultaneous respiratory epidemics. In 2022, however, substantial influenza transmission returned to Nicaragua where it co-circulated with severe acute respiratory syndrome coronavirus 2, causing substantial disease burden.